Penerapan E-Government melalui Whistleblowing System (WBS) dalam Pengawasan Penyelenggaraan Pemerintahan di Kabupaten Bulukumba - Andi Irpan Badawi; Ashar Prawitno (Research and Development Agency Ministry of Home Affairs, 2022)
The increase in vulnerabilities and violations demonstrates a concerning state of implementation in Indonesia, particularly in the public sector. The government has made numerous efforts, one of which is the implementation of e-Government through the Whistleblowing System (WBS). As a result, the goal of this research was to determine how the implementation of e-Government through WBS in supervising government administration in Bulukumba Regency. Therefore, the research method is qualitative research in order to reveal the data descriptively. According to the findings, the implementation of e-Government through WBS in Bulukumba Regency was not done optimally. This can be overcome by taking into account several factors that determine the success of e-government implementation, such as support, capacity, and value, in order to achieve optimal e-Government implementation.